Monitoring Tegangan, Arus, Dan Daya Secara Real Time untuk Perbaikan Faktor Daya Secara Otomatispada Jaringan Listrik Satu Fase Berbasis Arduino - Hidayat Nur Isnianto; Esti Puspitaningrum (Penelitian dan Pengabdian Kepada Masyarakat Sekolah Vokasi Universitas Gadjah Mada, 2018)
Electrical appliances in industrial and residential are now much inductive, consequently causing thepower factor value less than 1 (one), so the power capacity installed to the customer is not optimal.Power factor improvements are needed to improve the efficiency of active power usage so that it canbe maximized. To overcome this, a device is made to automatically improve the power factor due toinductive load changes, ie by installing capacitors in parallel to the source automatically using anArduino-controlled switch when the power factor value is less than 0.85. The test results show that thispower factor repair system is working automatically, real time and recorded on microSD. The powerfactor value can be up to 0.92 with 4.5 μF to 18 μF capacitors at inductive loads of 40 W to 225 Wwith error at 7.06% current sensor, 0.50% sensor, cos phi sensor 4.20%. All measurements aredisplayed on the LCD and recorder on SDCard.